2012
DOI: 10.1029/2011jf002278
|View full text |Cite
|
Sign up to set email alerts
|

Sediment entrainment by debris flows: In situ measurements from the headwaters of a steep catchment

Abstract: [1] Debris flows can dramatically increase their volume, and hence their destructive potential, by entraining sediment. Yet quantitative constraints on rates and mechanics of sediment entrainment by debris flows are limited. Using an in situ sensor network in the headwaters of a natural catchment we measured flow and bed properties during six erosive debris-flow events. Despite similar flow properties and thicknesses of bed sediment entrained across all events, time-averaged entrainment rates were significantl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
216
2

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 162 publications
(238 citation statements)
references
References 66 publications
20
216
2
Order By: Relevance
“…From large-scale debris-flow erosion experiments at the US Geological Survey debris flow flume, Reid et al (2011) reported erosion rates ranging from 0.05 to 0.10 ms −1 . McCoy et al (2012) reported a maximum erosion rate of about 0.14 ms −1 within the headwaters of a natural debris flow catchment at Chalk Cliffs, Colorado, USA. The maximum erosion rate measured in the Illgraben (0.25 ms −1 ) is somewhat larger than reported in the other studies; however, the flows at the Illgraben are also larger in size than in the other studies.…”
Section: Debris-flow Entrainment Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…From large-scale debris-flow erosion experiments at the US Geological Survey debris flow flume, Reid et al (2011) reported erosion rates ranging from 0.05 to 0.10 ms −1 . McCoy et al (2012) reported a maximum erosion rate of about 0.14 ms −1 within the headwaters of a natural debris flow catchment at Chalk Cliffs, Colorado, USA. The maximum erosion rate measured in the Illgraben (0.25 ms −1 ) is somewhat larger than reported in the other studies; however, the flows at the Illgraben are also larger in size than in the other studies.…”
Section: Debris-flow Entrainment Modelmentioning
confidence: 99%
“…Physically based numerical models were developed to investigate runout distance and inundation patterns as well as flow heights and flow velocities (Crosta et al, 2003;D'Ambrosio et al, 2003;Medina et al, 2008;Hungr and McDougall, 2009;Christen et al, 2012). Only recently have researchers focused on better understanding the process by which debris flows entrain sediment from the bed of a torrent channel as part of the erosion process (e.g., Hungr et al, 2005;Mangeney et al, 2007;Berger et al, 2011;McCoy et al, 2010McCoy et al, , 2012McCoy et al, , 2013.…”
Section: Introductionmentioning
confidence: 99%
“…Bearing in mind that the gravity current studied was a simple viscous Newtonian fluid, this transition layer is reminiscent of the mixing layer in Le and Pitman [19]; and the stepwise entrainment of debris in field studies [6,23] allows a qualitative comparison with our findings.…”
Section: Shear Profilesmentioning
confidence: 84%
“…Berger et al [6] used a scour sensor to measure erosion rates during debris flows and they found that entrainment of sediment occurred progressively, and was correlated with high pressure and pressure fluctuations near the flow front, caused by particle impacts. McCoy et al [23] also found progressive entrainment at the flow front, as well as during more dilute flows, but they found no correlation with flow depth and other bulk flow properties. Instead they found high entrainment rates to be caused by high-frequency pore-pressure fluctuations near the surface when the bed sediment was saturated.…”
Section: State Of Current Entrainment Researchmentioning
confidence: 95%
“…Erosion sensors, described by Berger et al (2010), are an exclusive version that can be constructed with more affordable materials (cf. McCoy et al, 2012).…”
Section: Organizational Aspectsmentioning
confidence: 99%